Pós-avaliação da previsão de demanda por transportes no Município de Fortaleza - Lopes Filho, José Iran de Oliveira (2003)
This M.Sc. thesis research has as its main objective to carry out a post-evaluation study of the planning process of Fortaleza’s transportation system during the time span between 70’s and 90’s. In the midst of a currentreality of vast use of analytical tools in forecasting transportation demand this research aims at the critical analysis of the PDTU –Fortaleza’s Urban Transportation Master Plan, released in 1983. This work is based upon the 1977 household origin-destination survey as well as the actual evolution of socioeconomic and land use variables and the plan’s recommendations for increasing capacity on the road and transit networks. It is believed that, starting from a characterization of the present reality basedon the 1996 household O/D survey and the field surveys made out by the METROFOR Fortaleza’s metro system), CTAFOR (Fortaleza’s traffic control system) studies and IBGE (Brazilian Institute for Geography and Statistic) it will be possible to portray the actual scenario of the plan’s horizon decade (90’s) and to compare it not only with that scenario which was foreseen by the planners who developed the PDTU, but also with the scenario forecasted by aggregate demand models, calibrated with the 70’s data and fed by the actual evolution of the socioeconomic and land use variables, observed 20 years later. The research has shown that the demand foreseen empiricaly for the planner was super-estimated to the plan’s horizon of PDTU. Even with the application of aggregated patterns calibrated with data collected at the end of the 70’s and fed with values that reflected the real evaluation of the social -economical variables. The simulated demand was superior to the one observed nowadays. Therefore, this study comparesthe difficulty of planning a long-term transportation system, even with the resources of the analysis-support of aggregated prediction of the demand, without a hard legislation of land use besides the lack of a continuous monitoring along its validity.